Emerging development in polymeric electrospun nanoscale mats for tissue regeneration: narrative review of the literature - Hamza Abu Owida; Muhammad Al-Ayyad; Jamal Al-Nabulsi; Nidal Turab; Mustafa Abdullah (Bulletin of Electrical Engineering and Informatics, 2023)
Tissue engineering is a cutting-edge discipline that brings together scientific and health-related, biological, and engineering principles in order to build tissue-engineered constructions able to restore or sustain the physiological properties of native tissue, or to marginally enhance those properties. This field is called "regenerative medicine". By constructing structures that are analogous to the extracellular matrix, it will be possible to improve the transmission of oxygen and nutrients, as well as the release of toxins during the process of tissue healing, all while simultaneously maturing tissues. Over the past few years, various studies have concentrated on looking at nanostructures in three dimensions with the goal of using them in tissue engineering. In this group of methods, electrospinning stands out as one of the most successful options. Over the course of the past few decades, a great number of nanofibrous scaffolds have been produced for the purpose of restoring and repairing damaged tissue. In this article, the engineering of new tissues using nanofibrous textures as scaffolds are reviewed. In addition, recent developments in tissue regeneration and the difficulties related to electrospinning are discussed in this article, along with their respective solutions.